A maximal domain for strategy-proof and no-vetoer rules in the multi-object choice model - Kantaro Hatsumi; Dolors Berga; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2011)
Following Barberà, Sonnenschein, and Zhou (1991, Econometrica 59, 595-609), we study rules (or social choice functions) through which agents select a subset from a set of objects. We investigate domains on which there exist nontrivial strategy-proof rules. We establish that the set of separable preferences is a maximal domain for the existence of rules satisfying strategyproofness and no-vetoer.
Keywords: C72; D71; H41; 330; social choice; public decision making; voting by committees; generalized median voter scheme; separable preference; Medianwähler-Modell; Nichtkooperatives Spiel; Soziale Wohlfahrtsfunktion; Theorie